Breast Meat Fatty Acid Profiling and Proteomic Analysis of Beijing-You Chicken During the Laying Period - Zhang, Jian; Zhuang, Hong; Cao, Jing; Geng, Ailian; Wang, Haihong; Chu, Qin; Yan, Zhixun; Zhang, Xiaoyue; Zhang, Yao; Liu, Huagui (Frontiers in Veterinary Science, 2022)
The disparity in fatty acids (FA) composition exhibits a significant impact on meat quality, however, the molecular regulatory mechanisms underlying this trait in chicken are far from clear. In this study, a total of 45 female Beijing-You chicken (BYC) hens, fed on the same diet, were collected at the slaughter age of 150, 300, or 450 days (D150, D300, and D450) from sexual maturation stage to culling stage (15 birds per age). Gas chromatography-mass spectrometry (GC-MS) and tandem mass tag labeling technology based on liquid chromatography mass spectrometry (TMT-LC-MS/MS) analysis strategies were applied to profile FA compositions and to compare differential expressed proteins (DEPs) between these different slaughter ages, respectively. The FA profiling showed that increasing hen ages resulted in increased contents of both saturated and unsaturated fatty acids. Proteomic analyses showed a total of 4935 proteins in chicken breast muscle with the false discovery rate (FDR) < 1% and 664 of them were differentially expressed (fold change > 1.50 or < 0.67 and P < 0.01). There were 410 up- and 116 down-regulated proteins in D150 vs. D300 group, 32 up- and 20 down-regulated in D150 vs. D450 group, and 72 up- and 241 down-regulated in D300 vs. D450 group. A total of 57 DEPs related to FA/lipid-related metabolisms were obtained according to the enrichment analysis of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). These DEPs were involved in 21 significantly enriched (P < 0.05) pathways, including well-known pathways for FA synthesis (metabolism, desaturation, and elongation) and the signaling pathways for lipid metabolism (PPAR, adipocytokine, calcium, VEGF, MAPK, and Wnt). In addition, there existed several representative DEPs (FABP, FABP3, apoA-Ⅰ, apoA-IV, apoC-Ⅲ, apoB, VTG1, and VTG2) involved in the regulation of FA/lipid transportation. The construction of the interaction networks indicated that HADH, ACAA2, HADHA, ACSL1, CD36, CPT1A, PPP3R1, and SPHK1 were the key core nodes. Finally, eight DEPs were quantified using parallel reaction monitoring (PRM) to validate the results from TMT analysis. These results expanded our understanding of how the laying age affects the FA compositions and metabolism in hen breast meat.